Topography and ultrasonographic identification of the equine pulmonary vein draining pattern. (April 2016) - Vandecasteele, T.; van Loon, G.; Vandevelde, K.; De Pauw, B.; Simoens, P.; Cornillie, P.
Highlights: Three of the four equine pulmonary vein ostia were observed during ultrasound recording. The orientation of the antrum of ostia 2 and 3 ensures that they are the most suitable for ultrasound measurements. The transverse orientation of the antrum of ostium 4 makes this ostium less suitable for flow measurements. Abstract: Information on ultrasound examination of equine pulmonary veins is scarce due to a lack of in-depth anatomical information. Each pulmonary vein drains a specific lung lobe region, after which those veins merge into a collecting antrum, before opening into the left atrium through their respective ostia. The aim of this study was, by using anatomical dissection and silicone casting of equine cardiopulmonary sets, to study the venous drainage of both lungs and the position of the ostia and to investigate whether the ostia can be identified and differentiated using ultrasound. Three out of the four ostia could be observed echocardiographically in the standing horse. The ostium draining the most caudal aspects of both lungs showed little variability, while the ostium draining the rest of the right lung could be used as an easily recognisable landmark, since it was located adjacent to the interatrial septum. The identification of the equine pulmonary vein ostia using ultrasound might allow for the determination of size and flow patterns in the assessment of cardiovascular disease.